2006
DOI: 10.1177/0095798406286801
|View full text |Cite
|
Sign up to set email alerts
|

Africentric Cultural Values: Their Relation to Positive Mental Health in African American Adolescent Girls

Abstract: The primary purpose of this study was to test a path model exploring the relationships among Africentric cultural values, self-esteem, perceived social support satisfaction, and life satisfaction in a sample of 147 African American adolescent girls. This investigation also examined the possible mediating effects of self-esteem and perceived social support satisfaction in the relationship between adherence to Africentric cultural values and life satisfaction in this sample. Although no significant mediating eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 29 publications
2
54
0
Order By: Relevance
“…For example, Constantine et al (2006) examined the relationships between Africentric cultural values, self-esteem, perceived social support satisfaction, and LS among a group of African-American adolescent girls and found LS to be positively related to adherence to Africentric values, and self-esteem, but not to perceived social support satisfaction (cf. Brown et al 2001).…”
Section: Cultural Valuesmentioning
confidence: 99%
“…For example, Constantine et al (2006) examined the relationships between Africentric cultural values, self-esteem, perceived social support satisfaction, and LS among a group of African-American adolescent girls and found LS to be positively related to adherence to Africentric values, and self-esteem, but not to perceived social support satisfaction (cf. Brown et al 2001).…”
Section: Cultural Valuesmentioning
confidence: 99%
“…Exposure to BSCs and African‐culture‐centered programming has been linked to increased self‐esteem (Livingston, McAdoo, & Mills, ) and academic motivation (Bass & Coleman, ), as well as stronger, more self‐determined identity statuses and positive overall self‐concept (Constantine, Alleyne, Wallace, & Franklin‐Jackson, ). Receiving messages that encourage cultural pride was also found to be predictive of lower psychological distress (Bynum, Burton, & Best, ).…”
Section: Examining the Black Studies Effectmentioning
confidence: 99%
“…Conversely, resistance to cultural changes, rejection of host culture, and preserved exclusion are accompanied by increased stress and other psychopathological symptoms (Berry et al 1987;Constantine et al 2006;Liebkind and Jasinskaja-Lahti 2000). For example, in predicting subjective wellbeing of Chinese international students in Australia, results revealed that strong host and co-national identifications of Chinese students promoted life satisfaction as well as positive psychological states (Zheng et al 2004).…”
Section: Acculturationmentioning
confidence: 99%